ARM9-Linux Karnel - Pradip Ram Selokar (International Journal of Reconfigurable and Embedded Systems (IJRES), 2016)
ARM9 supports the Linux Kernel. On a development system it is advantageous to load the Root File System (RFS) through Network File System (NFS). Several pieces of software are involved to boot a linux kernel on SAM9 products. First is the ROM code which is in charge to check if a valid application is present on supported media (FLASH, DATAFLASH, NANDFLASH, and SDCARD).